1981
DOI: 10.4039/ent113527-6
|View full text |Cite
|
Sign up to set email alerts
|

Variables Associated With Pheromone Traps for Monitoring Spruce Budworm Populations (Lepidoptera: Tortricidae)

Abstract: The effects of three trap variables (age, saturation, and density) on catches of male spruce budworm moths were tested using Pherocon 1CP® traps baited with synthetic sex attractant in high-density budworm populations in Maine and low-density populations in Ontario. As trap age increased, the number of moths captured decreased significantly; traps aged 2, 10, and 16 days caught an average of 5.4, 28, and 27% fewer moths than unaged traps. Traps functionally saturate and trapping efficiency diminishes in both h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 5 publications
3
37
0
Order By: Relevance
“…After identification of the sex pheromone itself (Table 1), some of the most important factors that influence the efficacy of a pheromone-based monitoring system are the lure type (Sanders and Meighen 1987), pheromone dose and the trap type (Evenden et al 1995b) and the trap spacing and density at each site (Houseweart et al 1981). Lure type and pheromone dose both can influence the active space (Byers 2008) of the pheromone plume and dictate the distance from which moths can be attracted and the period over which the lure remains attractive.…”
Section: Monitoring Forest Defoliatorsmentioning
confidence: 99%
“…After identification of the sex pheromone itself (Table 1), some of the most important factors that influence the efficacy of a pheromone-based monitoring system are the lure type (Sanders and Meighen 1987), pheromone dose and the trap type (Evenden et al 1995b) and the trap spacing and density at each site (Houseweart et al 1981). Lure type and pheromone dose both can influence the active space (Byers 2008) of the pheromone plume and dictate the distance from which moths can be attracted and the period over which the lure remains attractive.…”
Section: Monitoring Forest Defoliatorsmentioning
confidence: 99%
“…Brown (1984) shows linear regression equations on his increased trap capture data; however, the data are presented as "relative efficiencies" and related in various ways to the changing day-to-day efficiency of the traps, apparently buffering out the curvilinear nature of trap saturation, which is still hinted at by the graphed data. Others (Houseweart et al 1981;Riedl 1980;Sanders 1978Sanders , 1986 have also shown that trap saturation starts at some trap capture level and then trap capture begins to decline steadily from that point. We have demonstrated that for NOW, trap saturation progresses nonlinearly at densities below 50 moths per trap for all sticky traps tested, and also it progresses in a nonlinear manner above 50 moths per trap with the exception of the Trécé wing trap.…”
Section: Trap Captures Equationsmentioning
confidence: 99%
“…Previous studies of other insects have evaluated differences in trap design (Brown 1984;Knodel and Agnello 1990;Ramaswamy and Cardé 1982;Sanders 1978) and methods to increase trap capture (Houseweart et al 1981;Ramaswamy and Cardé 1982;Sanders 1986). Our interest, however, was in determining the trap saturation threshold and efficiency of the sticky traps that are industry standards for monitoring insects that are in the same size range as NOW.…”
Section: T He Navel Orangeworm (Now)mentioning
confidence: 99%
See 1 more Smart Citation
“…Catches may hâve been affected by saturation of trap bottoms or détérioration of trapped moths making identification difficult. Lure âge also may affect trapping through decreasing émission rates overtime (Housewart et al 1981). The field life of the pheromone lures used in this study is approximately 6-8 wk (J. Hansel, personal communication), so decreased émission rates should not hâve influenced catches.…”
mentioning
confidence: 99%